(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In current conditions in Kazakhstan society is growing interest in process of socialization and youth values, in that ambiguous political processes neighboring regions increase the interest of scientists on actual operating actors and identifying their resources, focus, and activity and forecast its impact on causes. Consideration impact of information on socialization youth value system is very important. Since the media – one of the most powerful transmitters of social experience, media activity in the socialization process of young people is extremely important. To stabilize these processes directed activities of state youth policy. Key words: young people, the process of socialization, values, media, youth policy.